Organophosphate Compound Poisoning - Shrestha, Sitaram (Journal of General Practice and Emergency Medicine of Nepal, 2011)
Acute organophosphorus (OP) pesticide poisoning is a major clinical problem in the developing world. 1, 2, 3 The World Health Organization (WHO) estimates the number of acute pesticide poisoning at 3 million cases per year and mortality of 3, 00,000deaths per year.4. Most of these pesticide poisoning and subsequent death occur in developing countries following a deliberate self ingestion of the poison. Metacid (Methyl Parathion) and Nuvan (Dichlorovos) is popular Organophosphorus compound used for deliberate self harm in Nepal The Organophosphorus inhibites cholinesterase activity leads to accumulation of acetylcholine at synapses, causing overstimulation and disruption of neurotransmission in both central and peripheral nervous systems. Exaggerated manifestations of nicotinic and muscarinic receptors appear as a result of these actions. Diagnosis of poisoning is done with history of exposure to pesticides, characteristic signs of toxicity and improvement of condition with Atropine. Supportive management of poisoning follows rapid initial management of airways, breathing and circulation Gastic lavage and administration of charcoal is done routinely with decontaminating procedure. Cholinesterase reactivates e is an important part of management, but benefit is not well confirmed in clinical trails.